Hemoglobin/myoglobin oxygen desaturation during Alpine skiing - Szmedra, L.; Im, J.; Nioka, S.; Chance, B.; Rundell, K. W. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To investigate muscle blood volume (BV) change and hemoglobin/myoglobin oxygen desaturation (OD) during simulated giant slalom (GS) and slalom (SL) Alpine ski racing. Methods: Joint angle, BV, OD, and heart rate (HR) were evaluated during GS and SL events in 30 junior elite skiers ages 9-17 yr (13.5 +/- 2.3). Subjects were stratified by ski class and age: group I, J1 and J2, ages 15-18 yr (16.8 +/- 0.8); group II, J3, 13-14 yr (13.6 +/- 0.7); and group III, J4 and J5, 9-12 yr (11.5 +/- 1.2). Near-infrared spectrophotometry (NIRS) was used to measure BV and OD in the capillary bed of the vastus lateralis during trials. Maximal OD was determined during thigh cuff ischemia (CI). Quadriceps cross-sectional area (CSA) was estimated by skin-fold and thigh circumference. Results: Joint angles were smaller (P < 0.05) during GS than SL for ankle (83.8 +/- 11.9 degrees; 98.6 +/- 15.7 degrees ), knee (107.4 +/- 14.9 degrees; 118.3 +/- 18.0 degrees ), and hip (98.8 +/- 14.3 degrees; 107.5 +/- 16.2 degrees ). BV reduction from rest to peak exercise (DeltaBV) was 30% greater (P < 0.05) during the GS than SL, whereas DeltaOD was 33% greater (P < 0.05) during GS. DeltaOD, relative to CI OD, was greater for all subjects during GS (79.2 +/- 3.7%) than SL (65.7 +/- 4.4%). This pattern continued within groups; group II displayed the greatest relative desaturation (82.9 +/- 7.6%). CSA was larger in older skiers (92.5 +/- 21.6; 72.5 +/- 12.3; 65.3 +/- 21.2 cm2) and correlated with DeltaOD (P < 0.05). Conclusion: The larger reduction in BV (DeltaBV change) and greater OD when skiers assumed lower posture during GS than SL may be related to greater effective static load secondary to higher percent of maximal voluntary contraction and is consistent with compromised blood flow to working muscle.